Data sharing in psychology: A survey on barriers and preconditions - Houtkoop, B; Chambers, C; MacLeod, M; Bishop, D; Nichols, T; Wagenmakers, E (SAGE Publications, 2018)
Despite its potential to accelerate academic progress in psychological science, public data sharing remains relatively uncommon. In order to discover the perceived barriers to public data sharing and possible means for lowering them, we conducted a survey, which elicited responses from 600 authors of articles in psychology. The results confirmed that data are shared only infrequently. Perceived barriers included respondents’ belief that sharing is not a common practice in their fields, their preference to share data only upon request, their perception that sharing requires extra work, and their lack of training in sharing data. Our survey suggests that strong encouragement from institutions, journals, and funders will be particularly effective in overcoming these barriers, in combination with educational materials that demonstrate where and how data can be shared effectively.